POLA MAKAN DENGAN PENCEGAHAN GOUT ARTRITIS - Ogelang, Michelle Jevania; Lamonge, Annastasia Sintia; Manibuy, Putri; Simpuru, Selin; Ngantung, Regina; Kum, Jobe; Walukow, Kaori; Oroh, Cindi T M; Lumintang, Cyntia Theresia (Lasalle Health Journal, 2024)
Introduction: Gout arthritis is one of the diseases that is widely experienced by the community and is a serious problem of non-communicable diseases at the international and national levels. Gout arthritis as a result of increased uric acid levels in the blood, can occur due to diet. Gout arthritis can have an impact on health, social life, and family economic conditions. Therefore, it is necessary to know the efforts to prevent gout arthritis. Objective: This study aims to determine the relationship between diet, both frequency and portion size, with the prevention of gout arthritis in the community in Winetin Village, RT II, ​​Talawaan District. Method: The research method used is quantitative with a descriptive analytical design and a correlation approach. The population is the local community aged > 17 years, totaling 132 people. The sample was taken using purposive sampling, with the Slovin formula, the number of samples was 100 respondents. Results: The results of the Spearman test showed a significant relationship between diet and the prevention of gout arthritis where diet (meal frequency and there was a significant relationship, and diet (meal portion) and there was a significant relationship. Conclusion: A good diet is one of the efforts to prevent gout arthritis. Regulating purine diet in terms of frequency and portion size is important.